Home away from home : the Caribbean Diasporan Church in the Black Atlantic tradition - Reid-Salmon, Delroy A. (London ; Oakville, CT : Equinox Pub., 2008)
"Home Away from Home explores how Caribbean diasporan people understand themselves in light of their faith in Jesus Christ, Taking the Caribbean diasporan experience as a source for theological discourse, the book argues that the faith Caribbean people brought with them into the diaspora plays a central role in their development." "The study identifies three forms of Caribbean diasporan identity, provides a theological interpretation of the diasporan experience, delineates the foundational theological principles, traces the patterns of and proposes the distinctives of the Caribbean diasporan church and thus, offers a Caribbean diasporan ecclesiology."--Jacket.
Introduction -- The Caribbean diasporan experience in Black theological discourse : a neglected sibbling -- Theorising the Caribbean diasporan identity : identifying ourselves -- Forging an identity for the Caribbean diaspora : knowing ourselves -- Standing on our own two feet : theological foundations of the Caribbean diasporan church --Theologizing diaspora : The theological heritage of the Caribbean diasporan church -- Pilgrims from the sun : the quest for survival -- Missionaries in the Caribbean diaspora : doing God's work in a new land -- A voice in the diaspora : seeking the welfare of the "city" resident homeland -- The distinctives of the Caribbean diasporan church.
Includes bibliographical references (pages 219-232).
Print version record.
Keywords: Caribbean Americans -- Religion; African diaspora; African Americans -- Religion; Black theology; Afroamerikanischer Synkretismus; Karibischer Einwanderer; Diaspora; Glaubensleben; RELIGION / Christianity / History; Electronic books